MIGRAR EN LA WEB. HISTORIA ORAL: CREANDO TERRITORIOS PARA LOS DERECHOS HUMANOS Y LA DEMOCRACIA - Spadaro, Gabriela Scartascini; Melchor, Vilma Zoraida RodrÃguez; Curiel, Guadalupe Talavera (European Scientific Journal, ESJ, 2015)
Impressive are the changes that have occurred to new communication technologies both in close interpersonal relations and with people who live in other countries. NET, Web, cloud or Internet, indiscriminately named and known worldwide, is the recipient of the immediacy of the informative shot of the image in real time, of the voices without voice, the power of networks, of a revolution that makes information even where Governments and dominant discourses proposed censorship. Such is the case of the countless files that exist on oral testimony that recovers the memory of actions that violate the human rights committed by dictatorial governments and that, in recent years, they have migrated by the web creating new frontiers of common histories, even when the facts have occurred thousands of kilometres away real. In this proposal, we will reflect on the new territories created by Oral history, starting from its global presence and strength in the speeches and citizen participation that is generated when it is presented in the memory files and revisionist readings on the Web, which has become the ideal medium for weaving a millionaire multiplication of voices and actions for human rights and democracy around the world.